FerriIridium: A Lysosome‐Targeting Iron(III)‐Activated Iridium(III) Prodrug for Chemotherapy in Gastric Cancer Cells. Issue 8 (21st January 2020) - Kuang, Shi; Liao, Xinxing; Zhang, Xianrui; Rees, Thomas W.; Guan, Ruilin; Xiong, Kai; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract: Reported is the Fe III ‐activated lysosome‐targeting prodrug FerriIridium for gastric cancer theranostics. It contains a meta ‐imino catechol group that can selectively bond to, and be oxidized by, free Fe III inside the cell. Subsequent oxidative rearrangement releases Fe II and hydrolyses the amine bond under acidic conditions, forming an aminobipyridyl Ir complex and 2‐hydroxybenzoquinone. Thus, Fe II catalyzes the Fenton reaction, transforming hydrogen peroxide into hydroxyl radicals, the benzoquinone compounds interfere with the respiratory chain, and conversion of the prodrug into the Ir complex leads to an increase in phosphorescence and toxicity. These properties, combined with the high Fe III content and acidity of cancer cells, make FerriIridium a selective and efficient theranostic agent (IC50 =9.22 μm for AGS cells vs. >200 μm for LO2 cells). FerriIridium is the first metal‐based compound that has been developed for chemotherapy using Fe III to enhance both selectivity and potency. Abstract : Double agent : The catechol‐containing iridium complex FerriIridium can be specifically activated by iron(III) to generate phosphorescence and cytotoxicity. FerriIridium is shown to be a highly efficient and selective theranostic agent for gastric cancer.